Asuhan Kebidanan pada Nifas Ny. M P2A1 di PMB Hj. Halimatus Sa’diyah, Amd. Keb Kota Banjarmasin Tahun 2025 - Umu Kulsum; Merlin Karinda; Mariani, Mariani (Pusat Riset dan Inovasi Nasional, 2025)
According to the World Health Organization (WHO) in 2023, approximately 260,000 women worldwide die each year due to pregnancy and childbirth complications, including during the postpartum period. Around 10–15% of mothers in developing countries experience psychological disorders after childbirth, such as depression and temporary anxiety. Constipation is one of the common complaints during the postpartum period, which may be caused by perineal trauma, pain, or fear of straining. If not properly managed, this condition can slow down the recovery process. The purpose of this case study is to provide standard postpartum midwifery care and education on postpartum exercises to help overcome constipation. The method used was descriptive with a SOAP approach. The author provided care to Mrs. M (P2A1) from April 4 to June 1, 2025, at PMB Hj. Halimatus Sa’diyah, A.Md.Keb, and at the client’s home. Education was delivered using leaflets and postpartum exercise videos. The results showed that Mrs. M (P2A1) experienced complaints of constipation and anxiety on the second postpartum visit (day 3), and these complaints improved after being educated about consuming papaya and performing postpartum exercises. Evaluation during the fourth postpartum visit showed that the mother had no complaints and had chosen a 3-month injectable contraceptive method.